2013
DOI: 10.1080/15528030.2012.739992
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness, Spirituality, and Existential Well-being Among HIV-Positive Gay, Bisexual, and Other MSM Age 50 and Over

Abstract: The religious and spiritual experiences of HIV-positive gay, bisexual, and other men who have sex with men (MSM) are severely understudied, especially among those over 50. However, literature supports that religious/spiritual experiences are related to both physical and mental health among older adults. In this exploratory analysis we assessed the relations that exist among a sample of HIV-positive gay, bisexual, and other MSM over 50 in regard to sociodemographic factors and two established measures of relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Preliminary analyses found that religious behaviors were higher for the African American and Latinx/Other participants in our sample relative to the White participants. These findings corroborate previous research suggesting a greater frequency of religious coping among African Americans and Latinx compared to Whites (Cotton et al, 2006; Hampton et al, 2013; Sutton & Parks, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Preliminary analyses found that religious behaviors were higher for the African American and Latinx/Other participants in our sample relative to the White participants. These findings corroborate previous research suggesting a greater frequency of religious coping among African Americans and Latinx compared to Whites (Cotton et al, 2006; Hampton et al, 2013; Sutton & Parks, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Gay and bisexual men may also have unique experiences that do not necessarily follow the same tragectory of being more relgious as they age. For example, a study with HIV positive gay and bisexual men found that the men were less likely to be spiritual or religious as they aged (Hampton et al, 2013). This suggests that there may be unique factors influencing the religious and spiritual beliefs of LGBT older adults that are worth investigating further.…”
Section: Religion and Spirituality In Lgbt Older Adultsmentioning
confidence: 99%
“…Although general research with bisexual individuals has increased over the past 40 years, much of it has focused on HIV or simply included bisexuals as an additional sexual category rather than the primary focus (Rust, 2009). Some research on faith and sexuality has included bisexual individuals as part of the population of study (Brennan-Ing, Seidel, Larson, & Karpiak, 2013;Buser, Goodrich, Luke, & Buser, 2011;Gold & Stewart, 2011;Hampton, Halkitis, Perez-Figueroa, & Kupprat, 2013;Page, Lindahl, & Malik, 2013;Rosenkrantz et al, 2016;Woodell, Kazyak, & Compton, 2015), but the percentages of participants in these studies who identify as bisexual range from 8% to 27%. Most do not include pansexual participants.…”
Section: Review Of the Literaturementioning
confidence: 99%